Pemetaan Genetik Virus Avian Influenza di Indonesia 2007 - Dharmayanti, NLP Indi; Indriani, R.; Hartawan, R.; Hewajuli, D.A.; Ratnawati, A.; Darminto, Darminto (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRACTGenetic Mapping of Indonesian Avian Influenza Viruses 2007.Department of agricultureimplements vaccination as one a tool to control of avian influenza disease. The vaccinationprogram use virus seed such as H5N1, H5N2 and H5N9. Such as vaccination program for otherdiseases, avian influenza vaccine program have lack implementation in the field. In 2007,department of agriculture evaluated the AI vaccination program such as the master seedvaccine that can be used. Result of the evaluation showed that 11 of AI vaccines that weredistributed in Indonesia did not give protection more than 60% to Indonesian isolates in 2006(A/Ck/Pwt-Wij/06). From this point and many AI cases in the field in 2007, the aim of thisstudy was to conduct genetic diversity of avian influenza viruses which have circulated inIndonesia region. We used virus isolation for propagate the viruses, RT-PCR for identificationand DNA sequencing on HA1 region to analysis genetic diversity for genetic mapping anduseful for master seed candidate. The result of the study showed that there were 6 group ofgenetic diversity in 2007; Isolates from group 1, 5 and 6 can be used for AI vaccine candidate.Key words: genetic mapping, genetic diversity and avian influenza viruses